If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5v + -1u) + -3(-1u + -4v) = 0 Reorder the terms: -3(-1u + 5v) + -3(-1u + -4v) = 0 (-1u * -3 + 5v * -3) + -3(-1u + -4v) = 0 (3u + -15v) + -3(-1u + -4v) = 0 3u + -15v + (-1u * -3 + -4v * -3) = 0 3u + -15v + (3u + 12v) = 0 Reorder the terms: 3u + 3u + -15v + 12v = 0 Combine like terms: 3u + 3u = 6u 6u + -15v + 12v = 0 Combine like terms: -15v + 12v = -3v 6u + -3v = 0 Solving 6u + -3v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3v' to each side of the equation. 6u + -3v + 3v = 0 + 3v Combine like terms: -3v + 3v = 0 6u + 0 = 0 + 3v 6u = 0 + 3v Remove the zero: 6u = 3v Divide each side by '6'. u = 0.5v Simplifying u = 0.5v
| x^3-3x=2 | | 3x+5=-2x-1 | | 7x-7/5=4x+10/6 | | 9/4y=27/8 | | Dx+Hy=L | | -b^2+5b-24=0 | | 0=68+3.4x | | 18x^2y^2-24xy^2+-36y^2=0 | | 10x-6x=2x-10 | | 2(w+4)=4 | | 7x-4y=10 | | 3x^5=21 | | 0=96+3.2x | | 2(q-6)=18 | | 490=-7(9x-16) | | f(x)=96+3.2x | | 3b/5b-7=8/11 | | -21/5=c-(-4/5) | | 4*y+3=-10 | | 8/3x-6=34-7/3x | | 4(x+4)=7x+13 | | x^2-3=2 | | 8y+40=10y | | X+3x+8=x+14 | | 4x+8=5x-7 | | 3y+5x=18 | | 4y-1+y+47=8y+50-5y | | 8/3=6/3x+2 | | 2/3(12-4x)=-3/4(x-5) | | y*y-2y-3=0 | | g(-3)+1=1-2x | | 7b+3-4b=30-3(b+4) |